DÜZENSİZ NAZOFARENKS ALANLARINA KOBALT-60 İLE RADYOTERAPİ UYGULAMALARINDA KORUMA BLOKLARININ DOZ PARAMETRELERİNE ETKİSİ - BAŞ, Murat; ALKAYA, Fadime; KEMİKLER, Gönül and GÜRSOY, Oğuz (Cerrahpaşa Medical Journal, 2019)
Background.- Shielding blocks for protection of vital organs within a radiation field give rise to changes in dose distribution of open field due to decreasing of scattered radiation from the shielded areas. Several methods have been used to calculate depth dose values for irregular fields. However, validity of such methods should be verified before routine use in clinic. Design.- In this study, measured percentage depth doses for selected irregular fields have been compared with percentage depth dose for fields obtained using equivalent squares (negative field) and [4x(A/P)] techniques. Dose rates for blocked and unblocked fields have been measured. Also, dose profiles for open fields at 0.5 cm and blocked fields for three depths.0.5, 5 and 10 cm depth . have been obtained and the effect of blocking on dose profile for open field has been investigated. Results.- When measured percentage DD for the selected fields were compared with percentage DD for equivalent squares techtechnique, the percentage difference was found 0.20 %-2.34 % in the nasopharyngeal fields since the block edge was close to central axis. When measured percentage DDs were compared with percentage DD for [4x (A/P)] technique, the percentage difference was found 0. 20 %-2.34 % for the nasopharygeal fields. But both techniques were convenient for percentage DD except points at block edge. When out-put values for selected blocked fields were compared with those of open fields, if blocked fields were less than 25 %, out-put of open fields could be used for irregular fields. Since blocks were close to center of the fields in cranial fields outputs were found to have 2%-3% difference from outputs of open fields. Conclusion.- The dose under the block for selected field was about 10 % of dose at d max.